A territorialização da cafeicultura no Planalto da Conquista/Bahia : transformações e contradições no espaço agrário - Soares, Venozina de Oliveira (2011)
This study aims to analyze the territorialization of Coffee Culture in the plateau of conquista, Bahia, considering the opposition agribusiness X peasantry. The research included the six major coffee producing districts of the Plateau : Vitória da Conquista, Barra do Choça, Ribeirão do largo, Encruzilhada, Planalto e Poções. Besides the theoretical study, we evaluated the changes and contradictions that have been promoted in agrarian space, the public policies for the agricultural sector, particularly those related to coffee production, the question of labor and manpower employed in the coffee, well as the main consequences of coffee in the territorial context. The study allowed the analysis of the contrary, that they understood the territorial capital from the coffee activity. The categories of analysis that supported the work were the "space" and "territory". The main elements of the empirical question of this study were justified and supported by field research. In all districts a land structure was identified with extensive concentration of small units that produce coffee, led of course by farmers / peasants, who live with the large and medium enterprises in agribusiness, now developing its activities in the small farming, now selling its manpower in the larger coffee farms. The journey of wheels‟ workers ranging from 10 to 12 hours a day, with a range of approximately one hour for lunch. This range is formal because in most cases is not used for rest, the worker sacrifices to collect a larger amount of coffee, trying to increase production. It was found that 64.1% of these workers coming from other municipalities, that is, they do a seasonal migration between municipalities throughout the sampling period, as will the search for properties that offer better conditions of wage, in other words, a greater production of coffee. Workers interviewed, found that 81% own their own homes, but most do not have adequate infrastructure, a factor that directly reflects the poor quality of life for workers. As for schooling, 70% have incomplete primary, 18% are illiterate and only 2% have the second degree. Thus, most are unaware of their rights and do not claim for improvements and labor rights. So dodge the situation, highlighting these facets, given the need to survive the dynamism of the capitalist mode of production, which contributed decisively to determine the relationship of subordination of the rural working class. It was noted also that the quickly population‟s growth has resulted in swelling and the consequent increase of urban socioeconomic problems, due to lack of infrastructure and investments in required public policies. This is because the public policies implemented in the Plateau are geared primarily to support the productive chain of coffee (PRONAF investments, the creation of Class Councils, Banks, Offices and agencies linked to all levels of government), lacking, therefore, greater attention to the diversification of agricultural production and other local investment policies in the agricultural sector in general.